Pelatihan Driver Ojek Online dalam Pelaksanaan Basic Life Support (BLS) di Wilayah RT 15 Kenali Besar Kota Jambi - Hasyim Kadri (Jurnal Abdimas Kesehatan (JAK), 2022)
First Aid in Accidents is first aid that must be given immediately to victims who get an accident or sudden illness quickly and right before the victim is taken to the hospital. The intended aid is providing basic life support to the victim before complete first aid is given by a doctor or other health worker. The problem that often occurs with online motorcycle taxis is that they are confused and do not know how to do the correct Basic Life Support (BLS) for accident victims due to lack of knowledge and skills, for that the most appropriate solution is to help train online motorcycle taxis to be able to perform basic life support The results obtained were 30 online motorcycle taxi drivers took part in BLS training activities which within 6 months were gradually implemented for the implementation of BLS management for pre-hospital assistance in the Jambi City area. From the evaluation results online motorcycle taxi drivers are able to understand material about BLS, There is an increase in knowledge between after being given training and assistance, able to practice BLS properly, Able to apply basic life support in providing pre-hospital assistance, Able to disseminate information that has been obtained to people closes.